The Role of Educators in Counceling Guidance Program with Student Disciplinary Behavior - Raudatul Jannah, Mila (Lembaga Bale Literasi, 2024)
This study aims to investigate the role of educators in the implementation of a counseling guidance program focused on managing students' disciplinary behavior. The focus of the study involves educators; understanding of the program, the strategies they apply in managing students' behavior, and their perception of the effectiveness of the counseling guidance program. The research method involved qualitative and quantitative data collection through questionnaires, interviews, and observations. Respondents involved educators from different levels of education. Data analysis was conducted using a mixed approach, integrating qualitative and quantitative findings to provide a holistic understanding. The findings showed that most educators had a good understanding of the counseling guidance program and recognized its important role in managing students' disciplinary behavior. The most commonly used strategies included the application of rewards and punishments, but there were variations in approaches, with some educators emphasizing preventive approaches and positive coaching. Perceptions of the program's effectiveness varied, but the majority of respondents saw it as a valuable tool in improving student's discipline. The main challenges educators faced involved a lack of time to provide individualized attention to students and variations in parental support. Recommendations for improvement involve additional training for educators increased parental involvement, and continuous evaluation of the program for better adjustment. The results of this study can contribute to the development of more effective educational policies and practices in managing students' disciplinary behavior.